Leigos para o Desenvolvimento NGDO Fundraising – does the satisfaction with the 'on-line’ organization foster the amount of donations? - Laureano, Raul M. S.; Abreu, M. E.; Hassamo, S. (VII Congreso Internacional de Casos Docentes en Marketing Público y No Lucrativo, 2015)
Leigos para o Desenvolvimento began its activity in 1986, a Non-Governmental Development Organization developing its main work in Portuguese former colonies. Like all the institution from the Third Sector, its activity is dependent on its donors for its sustainability. Moreover, today donors rely heavily on the information the not-for-profit organization spreads trough social media. And so the aim of this paper is to understand if there is a clear link between donor satisfaction with the organization website and the donations given to it. The study showed that there is such a link but it is connected with the Facebook activity. The Website strategy and content does not reveal, at a first sight, a direct impact on donations practices.